Strategi Personal Branding melalui Pemasaran Online di Era Globalisasi - Allya Ega Annisa hutauruk; Arisman purba; Danny Ajar Baskoro; Naomi simanjuntak; Putri dwi jelita waruwu; Selvia Santa Maria Siallagan (Jurnal Bisnis Inovatif dan Digital, 2024)
Personal branding has become a crucial element in building a strong professional identity in the era of globalization. Through online marketing, individuals can leverage various digital platforms to create and manage a consistent and appealing self-image. This research examines effective strategies for personal branding through online marketing, including the use of social media, blogs, and personal websites. The study also explores how digital technology has transformed the way people perceive and interact with personal branding. The results indicate that successful personal branding strategies require not only high-quality and authentic content but also a deep understanding of the target audience and the use of analytics to measure effectiveness. With the right approach, personal branding through online marketing can enhance professional visibility, career opportunities, and business networks.